2009
DOI: 10.1186/1471-2172-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined TLR2 and TLR4 ligation in the context of bacterial or helminth extracts in human monocyte derived dendritic cells: molecular correlates for Th1/Th2 polarization

Abstract: Background: Recognition of pathogens by dendritic cells (DCs) through interaction with pattern recognition receptors, including Toll like receptors (TLR), is crucial for the initiation of appropriate polarized T helper (Th) cell responses. Yet, the characteristics and differences in molecular profiles of DCs with different T cell polarizing capacities are still poorly defined. To address this issue, the molecular profile of human monocyte derived DCs was characterized after exposure to TLR4 ligand LPS in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 62 publications
3
70
0
1
Order By: Relevance
“…Our findings correlate with other studies on dendritic cells, as Schistosoma mansoni egg Ags reduce LPS-stimulated phosphorylation of p38, JNK, and ERK in murine dendritic cells (44). S. haematobium and Ascaris lumbricoides infections were shown to suppress LPS-induced p38 phosphorylation, but not ERK activation, in dendritic cells (45,46). Studies demonstrate that NF-kB 2/2 mice infected with Trichuris muris show increased susceptibility to infection, with impaired Th2/Treg immune responses and the phosphorylation of NF-kB and ERK supposed to be crucial in helminth-induced Th2 immune responses (47,48).…”
Section: Discussionsupporting
confidence: 81%
“…Our findings correlate with other studies on dendritic cells, as Schistosoma mansoni egg Ags reduce LPS-stimulated phosphorylation of p38, JNK, and ERK in murine dendritic cells (44). S. haematobium and Ascaris lumbricoides infections were shown to suppress LPS-induced p38 phosphorylation, but not ERK activation, in dendritic cells (45,46). Studies demonstrate that NF-kB 2/2 mice infected with Trichuris muris show increased susceptibility to infection, with impaired Th2/Treg immune responses and the phosphorylation of NF-kB and ERK supposed to be crucial in helminth-induced Th2 immune responses (47,48).…”
Section: Discussionsupporting
confidence: 81%
“…TLR have previously been shown to be involved in S. mansoni antigen recognition by DC [12,[14][15][16][17], and for this reason, we analyzed TLR expression in CD4 1 T cells from NOD and C57BL/6 mice. We found that both the mRNA and surface protein levels of TLR1 and TLR6 are significantly higher in NOD mouse CD4 1 T cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). Taking into considera- tion the involvement of TLR2 [12,[14][15][16][17] in S. mansoniinduced immunomodulation, the disparate response by NOD and C57BL/6 CD4 1 T cells to TLR2 ligation may provide a partial explanation for the differential response to SEA in the two strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations